2022
DOI: 10.3389/fninf.2022.971231
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning reveals interhemispheric somatosensory coherence as indicator of anesthetic depth

Abstract: The goal of this study was to identify features in mouse electrocorticogram recordings that indicate the depth of anesthesia as approximated by the administered anesthetic dosage. Anesthetic depth in laboratory animals must be precisely monitored and controlled. However, for the most common lab species (mice) few indicators useful for monitoring anesthetic depth have been established. We used electrocorticogram recordings in mice, coupled with peripheral stimulation, in order to identify features of brain acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…32 Electrocorticographic recordings in human subjects demonstrated that anesthesia affected predictive activity mostly on longer timescales and in higher, prefrontal cortical areas and only very little in the core auditory cortex. 60 In principle, we took great care to keep the anesthesia as shallow and constant as 61 which, together with our awake recordings, supports the notion that the Bayesian surprise signals reported here reflect an elementary and early cortical computation that is less subject to brain states or arousal levels.…”
Section: Discussionsupporting
confidence: 76%
“…32 Electrocorticographic recordings in human subjects demonstrated that anesthesia affected predictive activity mostly on longer timescales and in higher, prefrontal cortical areas and only very little in the core auditory cortex. 60 In principle, we took great care to keep the anesthesia as shallow and constant as 61 which, together with our awake recordings, supports the notion that the Bayesian surprise signals reported here reflect an elementary and early cortical computation that is less subject to brain states or arousal levels.…”
Section: Discussionsupporting
confidence: 76%
“…The machine learning technique of boosting builds models sequentially, starting with a smaller number of models and increasing the number of models in each iteration [41][42][43][44][45]. The most common boosting methods include adaptive boosting (AdaBoosting), gradient boosting (GBM), and extreme gradient boosting (XG Boost) [40,46,47].…”
Section: Ensemble Techniques: Bagging Random Forest and Boostingmentioning
confidence: 99%
“…Application to the Perioperative Setting (Key Finding) Supervised machine learning has become increasingly important in surgery, anesthesia, and perioperative care. Ensemble techniques, such as random forests and boosting, combine multiple models for improved prediction accuracy [41][42][43][44][45][46][47][48]. Neural network techniques are also being applied in anesthesiology and perioperative medicine to predict outcomes [51,53,56,57].…”
Section: Neural Networkmentioning
confidence: 99%